The development of computer peripheral device for radiation survey with a GPS locator - Wongsirojkul, Wasan; Thong-Aram, Decho; Pattarasumunt, Attaporn (Engineering and Applied Science Research, 2014)
This research aims to develop a peripheral interfacing device to personal computer via a USB port for gamma radiation survey with a GPS locator. This developed device can measure the exposure rate of gamma radiation ranging from 0 to 2000 mR/hr. The operation can be divided into 2 major parts: hardware and software. The hardware part consists of the Geiger-Mueller detector, high voltage supply circuit, signal conditioning circuit, microcontroller circuit for signals counting and data communication. The software part consists of the microcontroller controlled program and the Windows based program to serve for displaying and manipulating the data received from the microcontroller and GPS module. The device was tested with a Cs-137 gamma-ray source for exposure rate measurement. It was found that the maximum counting rate of the developed system was 1×104 cps with linear regression coefficient ( R2 ) and error of 0.9999 and 5.8% respectively. Furthermore, there are several advantages of the developed device; for instance, high efficiency, easy to use and low price.